Children’s psychological needs in furniture development toward satisfaction and marketability: a literature review - Zhu, Junfeng; Alli, Hassan; Md Ishak, Siti Mastura (Global Academy of Training and Research (GATR) Enterprise, 2024)
Children’s furniture has gradually become essential to China’s furniture market. Recently, the domestic children’s furniture market in China has paid less attention to children’s psychological needs and more to practical considerations like safety, health, size, and material. In children’s furniture, fulfilling children’s psychological needs is worthy of product satisfaction and marketability. The study aimed to evaluate the variables of children’s psychological needs towards satisfaction and marketability of children’s furniture. A comprehensive literature review was conducted to provide new insights into the topic under investigation and define the valuable variables of psychological needs for children’s furniture design. The results acknowledged 12 variables of children’s psychological needs that designers and manufacturers must consider during the design and development of children’s furniture to promote product satisfaction and marketability.